Histopathological spectrum and frequency of thyroid carcinomas in thyroidectomy Specimens: experience from a tertiary care hospital in Karachi - Rashid, Marium; Shahid, Ruqaiya; Nasim, Ayeman; Gulzar, Rubina (International Journal of Pathology, 2025)
Background: Thyroid cancer constitutes 92% of all endocrine malignancies, and ranks as the eighth most prevalent cancer in females.Methods: This descriptive cross-sectional study was conducted to determine the frequency and histopathological features of thyroid cancers in thyroidectomy specimens, at the Department of Histopathology, Dow University of Health Sciences, Ojha campus, Karachi. Histopathological data of 350 specimens was collected during the course of research, from June 2021 to June 2022.Results: Of the 350 thyroidectomies, benign thyroid lesions were diagnosed in 281 (80.3%), low-risk neoplasms in 8 (2.3%) and thyroid cancer in 61 (17.4%) cases. Neck swelling was the most common presentation, followed by solitary thyroid nodule. Total thyroidectomy was the preferred type of surgery for malignant cases and benign cases with compressive symptoms. Female-to-male ratio was 6:1. Papillary thyroid carcinoma was the most frequent malignant neoplasm, diagnosed in 42 thyroidectomies (68.9%), followed by follicular and medullary carcinomas, 5 cases each (8.2%). Poorly differentiated thyroid carcinoma was documented in 2 cases and only one case of anaplastic carcinoma was reported.  Most of the thyroid cancers were pathological stage T3.Conclusion: Thyroid cancers accounted for 17.4% of all thyroidectomy cases with a strong female predominance. Papillary thyroid carcinoma was the most common type and most cases presented at pT3 stage. This emphasizes the need for thorough clinical and radiological evaluation of neck swellings to enable timely diagnosis.